A wire-shaped flexible asymmetric supercapacitor based on carbon fiber coated with a metal oxide and a polymer1. Issue 25 (7th July 2015) - Liu, Weijie; Liu, Nishuang; Shi, Yuling; Chen, Ying; Yang, Congxing; Tao, Jiayou; Wang, Siliang; Wang, Yumei; Su, Jun; Li, Luying; Gao, Yihua
<x xml:space="preserve">Abstract</x> A flexible wire-shaped fiber asymmetric supercapacitor shows perfect bending properties, high performance and good cycling stability.